Highlights for the 6th International Ion Channel Conference: ion channel structure, function, disease and therapeutics - Limei Wang; Kewei Wang (Elsevier, 2017)
To foster communication and interactions amongst international scholars and scientists in the field of ion channel research, the 6th International Ion Channel Conference (IICC-2017) was held between June 23-27, 2017 in the eastern coastal city of Qingdao, China. The meeting consisted of 450 attendees and 130 speakers and poster presenters. The program consisted of research progress, new findings and ongoing studies that were focused on (1) Ion channel structure and function; (2) Ion channel physiology and human diseases; (3) Ion channels as targets for drug discovery; (4) Technological advances in ion channel research. An insightful overview was presented on the structure and function of the mechanotransduction channel Drosophila NOMPC (No mechanoreceptor potential C), a member of the transient receptor potential (TRP) channel family. Recent studies on Transmembrane protein 16 or Anoctamin-1 (TMEM16A, a member of the calcium-activated chloride channel [CaCC] family) were summarized as well. In addition, topics for ion channel regulation, homeostatic feedback and brain disorders were thoroughly discussed. The presentations at the IICC-2017 offer new insights into our understanding of ion channel structures and functions, and ion channels as targets for drug discovery.